Physicochemical Characterization and Antioxidant Activity of Humic Acids Isolated from Peat of Various Origins; Molecules; Vol. 23, iss. 4 - Zykova M. V. Maria; Schepetkin (Shchepyotkin) I. A. Igor Aleksandrovich; Belousov M. V. Mikhail Valerievich; Krivoshchekov S. V. Sergey Vladimirovich; Logvinova L. A. Lyudmila; Bratishko K. A. Kristina; Yusubov M. S. Mekhman Suleiman-Ogly (Suleimanovich); Romanenko S. V. Sergey Vladimirovich; Quinn M. T. Mark (2018, 2018)
Title screen